Pengaruh Komitmen Organisasi dan Budaya Organisasi Terhadap Produktivitas Kerja Karyawan PT. Perkebunan Nusantara X Ajong Gayasan Kabupaten Jember - Lisa Sukmawati (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This study aims to analyze the effect of organizational commitment and organizational culture on the work productivity of PT. Nusantara X Ajong Gayasan Plantation, Jember Regency. This research is quantitative research. To answer the objectives of the study, the data were analyzed using multiple linear regression analysis. To find out whether the hypothesis is rejected or accepted in this study, the t-test and f-test are used. To determine the percentage of the dependent variable caused by the independent variable, the coefficient of determination (R2) is used. The population in this study were employees of PT. Nusantara X Ajong Gayasan Plantation, Jember Regency. The sample was determined by saturated sampling and obtained 40 respondents as a sample. The results showed that: (1) Organizational commitment has a positive and significant effect on employee work productivity (2) Organizational culture has no positive and significant effect on employee work productivity (3) Organizational commitment and organizational culture have a simultaneous effect on employee work productivity. Keywords: Organizational Commitment; Organizational Culture; Employee Work Productivity.